2009
DOI: 10.1242/jcs.034199
|View full text |Cite
|
Sign up to set email alerts
|

Lipids regulate P2X7-receptor-dependent actin assembly by phagosomes via ADP translocation and ATP synthesis in the phagosome lumen

Abstract: Latex bead phagosomes isolated from J774 macrophages polymerize actin. We show here that five lipids – phosphatidylinositol-4-phosphate, phosphatidylinositol-(4,5)-bisphosphate, sphingosine-1-phosphate (S1P), ceramide-1-phosphate and phosphatidic acid – stimulate both actin assembly and transport of ADP across the phagosomal membrane into the lumen. Once there, this ADP is converted to ATP by adenylate kinase activity. High luminal ATP concentrations correlated well with phagosome actin assembly under differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
35
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 29 publications
(48 reference statements)
4
35
0
Order By: Relevance
“…3A, yellow arrows). Phagosome localization of P2X 7 has been shown by others (15). In our study, accumulation of P2X 7 is clearly seen at the point of attachment between a captured HPB cell and the HEK-293 cell (Fig.…”
Section: P2x 7 Expression On Hek-293 Cells Confers the Ability To Phasupporting
confidence: 86%
See 2 more Smart Citations
“…3A, yellow arrows). Phagosome localization of P2X 7 has been shown by others (15). In our study, accumulation of P2X 7 is clearly seen at the point of attachment between a captured HPB cell and the HEK-293 cell (Fig.…”
Section: P2x 7 Expression On Hek-293 Cells Confers the Ability To Phasupporting
confidence: 86%
“…We and others have shown that most cellular P2X 7 receptors are located intracellularly rather than on the cell surface (15,20,39). In this study, an increase of P2X 7 surface expression on phagocytes was observed following phagocytosis of either apoptotic cells or beads, similar to the upregulation of the P2X 4 receptor on THP-1 cells after phagocytosis of beads (40).…”
Section: Upregulation Of P2x 7 Surface Expression After Phagocytosissupporting
confidence: 71%
See 1 more Smart Citation
“…However, P2X7 receptors may play a role in linking innate and adaptive immunity after phagocytosis has occurred. Confocal microscopy shows P2X7 in the phagosome membrane surrounding engulfed particles or bacteria [29,30] and recent reports suggest that P2X7 together with pannexin-1 may facilitate the delivery of bacterial products from phagosome lumen into the cytosol, where they can activate inflammasome assembly [31,32]. Moreover P2X7 has a role in facilitating the fusion of phagosome with lysosome by a process involving stimulation of phospholipase D activity presumably on the phagolysosomal membrane [33,34].…”
Section: Non-opsonized Beadsmentioning
confidence: 94%
“…2 In addition to a cell surface residency, some P2XR subtypes are localized to intracellular compartments of mammalian and other eukaryotic cells, including lysosomes [7][8][9] and phagosomes. 10 In 2007 we cloned the first P2XR from a unicellular organism, from the amoeba Dictyostelium. 3 In contrast to the recognized cell surface role of P2XRs, the receptors of Dictyostelium are exclusively intracellular.…”
Section: Introductionmentioning
confidence: 99%